Finite element analysis of customized reconstruction plates for mandibular continuity defect therapy - Narra, Nathaniel; Valášek, Jiří; Hannula, Markus; Marcián, Petr; Sándor, George K; Hyttinen, Jari; Wolff, Jan (Journal of biomechanics, 2014)
Large mandibular continuity defects pose a significant challenge in oral maxillofacial surgery. One solution to this problem is to use computer-guided surgical planning and additive manufacturing technology to produce patient-specific reconstruction plates. However, when designing customized plates, it is important to assess potential biomechanical responses that may vary substantially depending on the size and geometry of the defect. The aim of this study was to assess the design of two customized plates using finite element method (FEM). These plates were designed for the reconstruction of the lower left mandibles of two ameloblastoma cases (patient 1/plate 1 and patient 2/plate 2) with large bone resections differing in both geometry and size. Simulations revealed maximum von Mises stresses of 63 MPa and 108 MPa in plates 1 and 2, and 65 MPa and 190 MPa in the fixation screws of patients 1 and 2. The equivalent strain induced in the bone at the screw-bone interface reached maximum values of 2739 micro-strain for patient 1 and 19,575 micro-strain for patient 2. The results demonstrate the influence of design on the stresses induced in the plate and screw bodies. Of particular note, however, are the differences in the induced strains. Unphysiologically high strains in bone adjacent to screws can cause micro-damage leading to bone resorption. This can adversely affect the anchoring capabilities of the screws. Thus, while custom plates offer optimal anatomical fit, attention should be paid to the expected physiological forces on the plates and the induced stresses and strains in the plate-screw-bone assembly.
Keywords: dospělí; Internal Fixators; Plastic Surgery Procedures; mandibula; Female; interní fixátory; Adult; počítačová simulace; ženské pohlaví; Tomography, X-Ray Computed; kostní šrouby; software; Finite Element Analysis; lidé; tlak; Mandible; zákroky plastické chirurgie; mechanický stres; Computer Simulation; Humans; Stress, Mechanical; Bone Plates; kostní destičky; Male; počítačové zpracování obrazu; Software; Pressure; analýza metodou konečných prvků; lidé středního věku; mužské pohlaví; Middle Aged; Image Processing, Computer-Assisted; Bone Screws; počítačová rentgenová tomografie